2016
DOI: 10.1159/000444331
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal-Septal Fasciocutaneous Flap Used as a Multifunctional Coverage for Prior Failed Hypospadias Repair

Abstract: Objectives: The study aims to report the method and outcome of using scrotal-septal fasciocutaneous flap as a multifunctional coverage for prior failed hypospadias repair. Methods: From January 2014 to June 2015, 18 hypospadias patients who have undergone repeated failed surgeries were enrolled. Their penile skin, urethral plate and dartos fascia are not enough to reconstruct the urethra, but have well-developed scrota. We performed urethroplasty by buccal mucosa free grafting and tubularized anastomosis 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chatterjee et al ( 24 ) reported 29 cases of hypospadias with testicular sheath covering the neourethra, and no incidences of urethrocutaneous fistula occurring after surgery. Zhang et al ( 25 ) reported on 18 cases of a scrotal-septal fasciocutaneous flap being used to cover the surface of anastomotic urethra, all achieving good results. These healthy tissues of autologous origin, especially the tunica vaginalis spongiosum, are the ideal replacement for the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al ( 24 ) reported 29 cases of hypospadias with testicular sheath covering the neourethra, and no incidences of urethrocutaneous fistula occurring after surgery. Zhang et al ( 25 ) reported on 18 cases of a scrotal-septal fasciocutaneous flap being used to cover the surface of anastomotic urethra, all achieving good results. These healthy tissues of autologous origin, especially the tunica vaginalis spongiosum, are the ideal replacement for the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…The use of well-vascularized tissue as a protective intermediate layer between the neourethra and the skin is considered an effective measure to prevent urinary fistula, and various tissues (e.g., dartos, de-epithelialized penile skin flap, tunica vaginalis, and corpus spongiosum) have been used (9)(10)(11)(12). In 2000, Beaudoin and Yerkes first reported the separation of two branches of the bifurcated urethral spongiosum, which were combined and then used to cover the ventral side of the new urethra, this procedure was termed "spongioplasty" (13,14).…”
Section: Discussionmentioning
confidence: 99%